The Royal College of Ophthalmologists’ National Ophthalmology Database study of cataract surgery: report 16, influence of remuneration model on choice of intraocular lens in the UK - Ting, Darren S. J.; Tatham, Andrew J.; Donachie, Paul H. J.; Buchan, John C. (Eye (London), 2023)
Background/Objectives Cataract surgery with intraocular lens (IOL) implantation is one of the most commonly performed surgeries worldwide. Within the UK, publicly funded cataract surgery is remunerated by two models: (1) “block contract” (BC), which commissions organisations to deliver whole service pathways without considering specific activity items; or (2) “payment by results” (PbR), which pays a tariff price for each procedure. This study aimed to examine the association between remuneration model and the cost and types of IOL used. Subjects/Methods Cataract operations recorded on the Royal College of Ophthalmologists’ National Ophthalmology Database were included, with additional data collected for remuneration model from NHS England and cost of IOL from the NHS Spend Comparison Service. Results We included 907,052 cataract operations from 87 centres. The majority of operations were performed in PbR centres (456 198, 50.3%), followed by BC centres (240 641, 26.5%) and mixed models centres (210 213, 23.2%). The mean price of hydrophobic ( n = 7) and hydrophilic IOLs ( n = 5) were £45.72 and £42.86, respectively. Hydrophobic IOLs were predominantly used (650 633, 71.7%) and were significantly more commonly used in centres remunerated by BC (96.5% vs. 3.5%) than those by PbR (65.7% vs. 34.3%) when compared to hydrophilic IOLs ( p < 0.001). Conclusions This study demonstrated that the IOL choice may be perversely incentivised by the IOL cost and remuneration model. Although hydrophobic IOLs are more expensive at the point of surgery, their potential longer-term cost-effectiveness due to reduced requirement for YAG capsulotomy should be considered.